Barriers and facilitators to primary healthcare encounters as reported by autistic adults: a qualitative study - Stein Duker, Leah I.; Giffin, Willa; Taylor, Elinor E.; Shkhyan, Lily; Pomponio Davidson, Amber; Mosqueda, Laura (Frontiers in Medicine, 2025)
BackgroundPrimary care is designed to co-manage health concerns, contribute to preventive care, and provide medical care coordination. Receiving primary care may be especially vital for autistic people, many of whom disproportionately experience psychiatric and physical health conditions. However, autistic adults often face barriers to receiving primary care, and first-hand accounts of these challenges are limited. Therefore, the purpose of this study was to describe barriers and facilitators to primary care encounters as reported by autistic adults.MethodsInterviews were conducted with 34 autistic adults in Los Angeles and Philadelphia, lasted an average of 26 min, were transcribed verbatim, and analyzed using thematic analysis. This dataset is part of a larger study that interviewed autistic adults, caregivers, and primary care providers (PCPs).ResultsParticipants were primarily White, non-Hispanic, and had a mean age of 32 years. Five overarching themes describing challenges and potential strategies to improve care emerged from the interviews: (1) finding a primary care provider, (2) the physical environment, (3) communication, (4) autism-specific knowledge, and (5) support for primary care encounters, while simultaneously highlighting the importance of tailoring care for autistic adults to improve primary care experiences. Results, specifically in the communication and autism-specific knowledge themes, were consistent with the neurodiversity model of autism, as participants highlighted stigma and mutual communication as key healthcare barriers.ConclusionFindings provide a nuanced understanding of autistic adult participants’ primary care experiences, highlighting their perception of barriers and facilitators to these healthcare encounters. These results offer valuable insights for improving the accessibility and quality of care for autistic people, many of which are practical, low/no cost, and easy to implement. Strategies also emphasized the diversity of experiences and preferences for autistic patients, highlighting the importance of tailoring accommodations in the primary care setting.